Reshaping youth participation : Manchester in a European gaze - McMahon, Gráinne; Rowley, Harriet; Batsleer, Janet (Emerald Publishing Limited, 2022)
Reshaping Youth Participation reframes discussions around youth political, social, civic, and cultural participation. Drawing upon insights on democracy and citizenship, self-organising and protest movements, and arts activism as engaged social activism, the chapters consider the youth participation spaces in which young people find voice and action-spaces that are part of existing forms of participation, and newly emergent spaces that challenge existing systems. Set in Manchester, Reshaping Youth Participation contextualises youth participation in a major UK city known for its activism and regional devolution, alongside studies from partner European cities. Exploring the participation of young people in 'adult spaces', of young people who are pursuing a new politics and ideological change, of marginalised young people, and of young people utilising the creative arts as a 'lived politics', the authors argue that youth participation provides a vital addition to sustaining and developing political, social, and democratic life in cities. Celebrating youth participation and its myriad forms, triumphs, and challenges, this edited collection provides much needed innovative thinking to the study of youth participation. It is an important contribution for young people themselves, academics, policymakers, local policy experts and makers, local activists, and community advocates.
Keywords: Youth -- Political activity -- England -- Manchester.; Youth -- Political activity -- Europe.; Political participation -- England -- Manchester.; Political participation -- Europe.; Political Science -- Political Process -- General.; Political structure & processes.; elektronické knihy; electronic books